The use of the ‘sponsa Christi’ metaphor by Cyprian of Carthage as a strategy to discipline the Christian virgin - Soares, Carolline da Silva (Romanitas - Revista de Estudos Grecolatinos, 2018)
The Carthaginian bishop Cyprian of Carthage wrote in 249 a treatise entitled De habitu uirginum, where he presents the Christian virgins as virtuous women, but also points out the cautions and precautions they must have in relation to the temptations of the world, which may lead them to abandon their chastity and, especially, their pudicitia. In his discourse, Cyprian uses his persuasive rhetoric to try to persuade the virgin to follow her determinations and disciplinary norms, for this reason, he uses as a strategy – a concept create by De Certeau – to use the metaphor sponsa Christi – Christ’s wife – emphasizing the meaning and importance of this sentence, in order to justify the exemplary behavior that he expects to be performed by the Christian virgin, based on modesty and obedience.